Relationship between Marketing, Service Quality and Satisfaction on Customer Loyalty Of Bank Syariah Mandiri Banyuwangi - Ratnasari, Dwi; -, Sasongko (Review of Management and Entrepreneurship, 2019)
The purpose of this study is to examine the effect of the relationship between marketing, service quality, and satisfaction on customer loyalty of Bank Syariah Mandiri in Banyuwangi district. The samples consist of 150 customers of Bank Sharia Mandiri Banyuwangi. Samples were chosen by accidental sampling. Data were analyzed using multiple regression. The research findings reveal that relationship marketing, quality of service, and customer satisfaction have positive and significant effect on customer loyalty.